A selected historical analysis of the “Complete High School” Maize Kansas - Botts, Kenneth Christopher (Kansas State University, 2015)
School districts throughout the United States have continuous concerns about how to meet the needs of high school students who are at-risk of dropping out of school. Despite multiple resources available for addressing this concern through alternative education schools and programs, there continues to be an unacceptably high number of students who do not graduate from high school. While knowledge about what is working in alternative schools and the students they serve is progressing, additional research is still needed. In Maize USD 266, Complete High School Maize is an award-winning and nationally recognized dropout prevention program that has, over a fifteen year span (1999-2014), helped reduce the dropout rate in Maize. The intent of this qualitative historical analysis was to serve two purposes. First, it delineated the historical evolution of Complete High School Maize as a model for school districts to emulate in an effort to reduce the number of high school dropouts. Secondly, this study provided historical documentation to help preserve and share in the history of the program for future generations of students. This study examined the factors and circumstances present in Maize USD 266 that resulted in the creation of an alternative school for its students. This study also narrated the structural evolution of Complete High School Maize from 1999 to 2014 and examined the conditions and factors that resulted in the progressions. The findings of the study showed that Complete High School Maize had successfully helped reduce the number of dropouts in Maize USD 266.
Keywords: Alternative school; alternative education; Complete High School Maize; Maize, Kansas; Educational leadership (0449)